Towards energy-efficient indoor environment quality using artificial intelligence: A bibliometric analysis - Lim, S.C.J.; Tee, Boon Tuan; Siew, P.W.; Lee, M.F. (2024)
With the increasing awareness of sustainability in the built environment, there is a pressing need to achieve a comfortable and healthy indoor environment with optimized energy consumption. In this context, artificial intelligence (AI) has shown its potential as a tool for energy optimization while upholding high IEQ standards. This research paper explores the current and future research trends in utilizing AI to achieve an energy-efficient indoor environment quality (IEQ). Bibliometric analysis is used as a methodology to identify key research themes and the thematic evolution of a research field. Based on a carefully formulated search term, a case study is performed using bibliometric data downloaded from the SCOPUS database. Upon data pre-processing steps, the research evolution of the field is presented visually using strategic mapping and thematic evolution networks over the years 2018-2023, with discovered insights discussed. Finally, some discussion on future works is given based on key insights.